Increased efficiency of combined heat and power plants by utilizing waste heat for resorption chillers and their combination with hydrocarbon chillers. (August 2020) - Ziegler, O; Hesse, U; Thomas, C
Abstract: The use of waste heat has long been a topic to increase the efficiency of large-scale industrial processes, but it is becoming as well important in the commercial sector and in small and medium-sized industrial plants. For a sustainable and decentralized energy supply it is necessary to utilize all exergy flows much more than before. Particularly in decentralized combined heat and power (CHP) plants, the annual coefficient of performance is low due to seasonal temperature fluctuations, as the generated heat cannot be used or can only be used partly during the summer and transitional months. Interface technologies such as sorption technology can be used to further increase the utilization rate of such CHP plants and provide cooling capacity at the same time. This concept allows the utilization of previously unused waste heat to generate cooling in the temperature range from -6°C to 15°C, without the necessity of significant amounts of electric energy for the operation of additional compression refrigeration systems. In a pilot project funded by the German Federal Ministry of Economic Affairs and Energy, a thermally driven refrigeration plant with a small cooling capacity of maximum 25 kW using the resorption principle was evolved under these aspects and installed in a supermarket. Special focus is given to the flexibility of the plant technology as well as to the potentials of combinations of thermally and electrically driven chillers with natural refrigerants such as hydrocarbons and ammonia and the integration of thermal storage for temporal decoupling or discontinuous availability of heat and cooling load.